Self-Control in Intertemporal Choice and Mediterranean Dietary Pattern - Muñoz Torrecillas, María J.; Cruz Rambaud, Salvador; Takahashi, Taiki (Frontiers in Public Health, 2018)
Background: The Mediterranean Diet (hereinafter MD) is considered a healthy dietary pattern. Adherence to this pattern can be assessed by means of the KIDMED test by which individuals are assigned an index and classified into three groups of adherence to MD: high, medium, and low. In addition, impulsivity or impatience in intertemporal choice has been defined as a strong preference for small immediate rewards over large delayed ones. Objective: This study examines the relationship between dietary habits, specifically Mediterranean dietary pattern, measured by the KIDMED index, and the exhibited impatience in intertemporal choices, by means of the parameter k (discount rate of the hyperbolic discount function). Methods: A sample of 207 university students answered a questionnaire based on two tests: the KIDMED test, to assess the degree of adherence to MD, and an intertemporal choice questionnaire, to assess impatience or impulsivity. Individuals were grouped depending on their KIDMED score and then the discount rate or impulsivity parameter was calculated for each group. Results: Discount rates were inversely related to the degree of adherence to MD. The values of overall k were 1.53, 1.91, and 3.71% for the groups exhibiting high, medium and low adherence to MD, respectively. We also found higher k-values for larger rewards (magnitude effect) in the three groups. Conclusion: High adherence to MD is related to less steep time discounting, which implies less impulsivity (more self-control) or lower discount rates. Conversely, low adherence to MD is related to steeper time discounting, which implies impulsivity or higher discount rates. These findings could be used to identify the target population where policy interventions are needed in order to promote healthier diet habits.